STRATEGI MERKETING BISNIS ONLINE DENGAN PROGRAM LEARNING ABOUT FACEBOOK (LAAF) DI KELOMPOK USAHA BISNIS KITA, SAWOJAJAR, MALANG, JAWA TIMUR - Ririn Noviyanti (Bulletin of Community Service and Development, 2021)
Purpose of the study: the realization of an online business that is strong and has high competitiveness and the realization of an online business that is able to survive in various seasons and at all times. Methodology: In this assistance, the first thing to do is to analyze the strengths and weaknesses contained in BK. BK's strength is that it has a variety of products, all of which have high branding among the public. The products provided by BK are appropriate and can be a solution for people who need them. Main Findings: Prior to Mentoring, participants did not take care of the team or were indifferent to the marketer team. Greetings to the team are only done in the morning accompanied by product knowledge, which is the task of the agent or leader to pass it on to marketers. Group is not alive. In a sense, there is no interaction that is more of a sense of kinship. Interaction tends to be the relationship between the agent and the leader or the leader and the marketer. This creates a wide divider. Applications of this study: Application learning all about facebook (LAAF) Our Business Group, Sawojajar, Malang, East Java Novelty/Originality of this study: In this service, we have been able to identify the problems experienced by the company owner, especially the problem of human resources or the ability of marketers to market a product.